Direct Torque Control of MMC FED 3-Phase Induction Motor Using Fuzzy Logic Controller - Mr.Sriramulu Naik Mudhavath, Dr.Gudapati Sambasiva Rao (International Journal of Advanced Science and Technology, 2020)
This work presents Direct Torque Control (DTC) of 3- phase Induction Motor (IM) fed from 3-level Modular Multilevel Converter (MMC) using Fuzzy Logic Controller (FLC). DTC has excellent control strategies of torque and flux for induction motor. DTC drives utilizing conventional hysteresis controllers suffering from high torque ripple and variable switching frequency. The proposed scheme fuzzy logic controller reduces the disadvantages torque, flux ripples, and merits of transient responses using MATLAB/SIMULINK. Keywords- Induction Motor, Direct Torque Control (DTC), Modular Multilevel Converter (MMC), Fuzzy Logic Controller (FLC).